Corporate Networks and business influence in Panama, Costa Rica, and El Salvador. - Robles Rivera, Francisco Javier (2021)
This paper explores the relationship between corporate networks and business influence to figure out the conditions of state capture. Methodology: We analyze corporate networks through interlocking directorates in three Central American countries – Panama, Costa Rica, and El Salvador – using network analysis, and we pinpoint the relationship between the structure of the corporate network and two corporate political actions: contributions to presidential campaigns and revolving doors. Conclusions: Results show corporate networks were fragmented in the three Central American countries, except for a well-connected business cluster in Panama. The organization of business elites based on a single cohesive business cluster could facilitate coordination to finance political parties, which gives them more strength to demand government posts. On the other side, the absence of connections between business elites makes it difficult to reach agreements and weaken business influence. Findings suggest that networking among some (not all) business elites can be a source that precedes state capture, as it organizes access to the state through collective mobilization of resources and coordinated action planning. Originality: This paper is the first study on networks of interlocking directorates in Central American economies and combines original data on contributions to electoral campaigns and revolving doors. Therefore, it can be a benchmark for future studies on business power. In addition, this study introduces the analysis of interlocking directorates in the literature on state capture.